PKM Penguatan Literasi Sekolah Melalui Mading Sastra Siswa SDN 149 Amessangeng Soppeng Sulawesi Selatan - Nurhalisa; Aslan Abidin; Juanda; Andi Nurul Fitriani (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
The goal to be achieved in PKM activities to strengthen School Literacy at SDN 149 Amessangeng through literary magazines is to increase students' interest in school literacy, especially in the field of literature, and to provide space for students to develop interests and talents in literature. Based on the results of the author's observations at SDN 149 Amessangeng there are still many children in grades 4-6 who do not know how to read. The method used is direct observation and assistance, such as providing explanations about magazines and their functions, holding workshops on how to write good poetry, accompanying poetry readings, and assisting in arranging the layout of literary magazines. Students work together with teachers at SDN 149 Amessangeng, to be precise in Goarie Village, Marioriwawo District, Soppeng Regency. The results obtained in this training were those elementary school students were able to compose poetry and they participated in the school madding.